(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
The protection of the mental health of detained persons continues to be a forgotten (or deliberately ignored) issue by our legislator. None of the reform proposals, including those of government initiative, relating to this aspect has in fact been included in the regulatory measures to amend the penitentiary system, which – amidst reluctance and timidity – have been approved in recent years. In the paper, an attempt is made to outline the possible contribution of substantial criminal law to the urgent redesign of the model of treatment and care of mental distress in prison and of supervening insanity. The limited adjustments made through the work of the jurisprudence, including constitutional ones, are not in fact sufficient to deal with a situation whose dramatic nature is made evident by the shocking number of suicides in prison (84 last year).